Naufragios en la costa de Bizkaia (1550-1800) - Ekain Cagigal (Mélanges de la Casa de Velázquez, 2023)
Shipwreck involves the darkest side of early modern maritime navigation and trade. Nonetheless, it is a socioeconomic and human feature of the marine communities, not deeply addressed for this period in the Biscayan coastline hitherto.Fortunately, documentary sources of Biscay provide valuable historical information for a better description of this phenomenon in geographical, commercial, socio-economical, and human terms. Aiming this ambition, as a result of this research work a database was built compiling nearly 200 shipwrecks along the Biscayan shoreline for the period 1550-1800, including cartographic material. Based on this evidence an extensive study was performed regarding distribution of wrecks location, diachronic evolution, causes of grounding, affected classes of vessel, and other remarks.